Symbols as a Medium of Theme Reflection in Paolini’s Inheritance: Eragon - Lanny Kusumawati; Deta Maria Sri Darta (Dinamika Bahasa dan Budaya, 2008)
In the writers’ opinion, there are two types of novel: those which are made for fun and leisure, and those which are compiled to deliver an idea(s). Based on that, the writers think that the novel used in this study, Eragon, is a novel which is such an attractive one to keep up with in addition to the moral values about life intended to deliver. Christopher Paolini, the author, has demonstrated every effort to write such a highly valued novel in the age of fifteen. This paper discusses the symbols in Paolini’s Inheritance: Eragon. There are two main points that this paper attempts to answer: (1) the symbols which are used in this novel and (2) how the theme is reflected by the symbols. Although there are many standpoints to observe in the novel, this paper only focuses on the work itself and the internal characteristics that build the story. Key words: symbol, theme, setting